FAKTOR – FAKTOR YANG MEMPENGARUHI KONSERVATISME AKUNTANSI DENGAN LEVERAGE SEBAGAI MODERASI - Angela Veronica; Widyasari Widyasari (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to observe the effect of institutional ownership, company size, and conflict of interest on accounting conservatism in manufacturing industry that was listed in Indonesia Stock Exchange during the research period. The study period starts from January 1, 2018 to December 31, 2020. The research finds that fixed effect model is the best model used in this study. Independent variables which are institutional ownership and conflict of interest were found not affect accounting conservatism significantly. However, this study found that company size had positive and significant effect to the accounting conservatism level. Leverage as a moderating variable was found not able to moderateeach independent variables on accounting conservatism.